Kajian Yuridis Peran Tentara Nasional Indonesia (TNI) Dalam Operasi Militer Selain Perang (OMSP) terkait Penanggulangan Tindak Pidana Terorisme - Ikhwan Syahdi; Sujono (CV. Era Digital Nusantara, 2024)
The issue of the involvement of the Indonesian National Army in handling criminal acts of terrorism which will be accommodated through law has sparked public concern about the possibility of a shift in the mechanism for handling terrorism in Indonesia from a criminal justice model that prioritizes law enforcement, to a war model that prioritizes the deployment of military capacity. The title of this research is a Juridical Study of the Role of the Indonesian National Army (TNI) in Military Operations Other Than War (OMSP) Related to Countering Criminal Terrorism. Problem formulation: What is the legal review of the role of the Indonesian National Army (TNI) in military operations other than war related to handling criminal acts of terrorism based on applicable laws and regulations? What is the legal position and constraints of the Indonesian National Army in dealing with acts of terrorism? The research was carried out using a normative juridical approach. The data used is primary, secondary and tertiary data. Data analysis was carried out qualitatively and based on the results of the analysis, conclusions were then drawn using a deductive approach. The conclusion of this research is that through military operations other than war, the role of the TNI is not only limited to the military dimension, but also expands its function as a security guard in situations that threaten national order, although its position in the context of civil and military law is often debated. The TNI can operate under coordination with the police in accordance with Law no. 5 of 2018 concerning Eradication of Criminal Acts of Terrorism. However, this regulation has a weakness, namely that there is no operational mechanism that regulates the implementation of TNI assistance tasks.